Rupture mechanism and seismotectonics of the Ms6.5 Ludian earthquake inferred from three‐dimensional magnetotelluric imaging. Issue 3 (4th February 2017) - Cai, Juntao; Chen, Xiaobin; Xu, Xiwei; Tang, Ji; Wang, Lifeng; Guo, Chunling; Han, Bing; Dong, Zeyi
Abstract: A three‐dimensional (3‐D) resistivity model around the 2014 Ms 6.5 Ludian earthquake was obtained. The model shows that the aftershocks were mainly distributed in a shallow inverse L‐shaped conductive angular region surrounded by resistive structures. The presences of this shallow conductive zone may be the key factor leading to the severe damage and surface rupture of the Ludian earthquake. A northwest trending local resistive belt along the Baogunao‐Xiaohe fault interrupts the northeast trending conductive zone at the Zhaotong‐Lianfeng fault zone in the middle crust, which may be the seismogenic structure of the main shock. Based on the 3‐D electrical model, combining with GPS, thermal structure, and seismic survey results, a geodynamic model is proposed to interpret the seismotectonics, deep seismogenic background, and deformation characterized by a sinistral strike slip with a tensile component of the Ludian earthquake. Key Points: The electrical structure constrains the distribution of the aftershocks characterizing the earthquake rupture A local resistive belt interrupts a large conductive zone, which can form the seismogenic structure of large to moderate earthquake Under the constraints of the preexisting structure, weakened conductive materials can produce new superimposed deformation